Plant AT-rich protein and zinc-binding protein (PLATZ) family in Dendrobium huoshanense: identification, evolution and expression analysis - Fangli Gu; Yanshuang Ren; Muhammad Aamir Manzoor; Tingting Wang; Renshu Huang; Naifu Chen; Cheng Song; Yingyu Zhang (BMC Plant Biology)
Abstract PLATZ (plant A/T-rich protein and zinc-binding protein) transcription factors are essential for plant growth, development, and responses to abiotic stress. The regulatory role of PLATZ genes in the environmental adaptation of D. huoshanense is inadequately comprehended. The genome-wide identification of D. huoshanense elucidates the functions and regulatory processes of the gene family. Our investigation encompassed the examination of PLATZ gene structures and chromosome distribution, the construction of the phylogenetic tree with its relatives, and the analysis of the cis-acting elements and expression profiles potentially implicated in growth and stress responses. Eleven DhPLATZs were classified into three clades (I, II, and III) according to their evolutionary homology. The distribution of these genes over six chromosomes indicated that both whole genome duplication (WGD) and segmental duplication events have contributed to the expansion of this gene family. The Ka/Ks analysis revealed a pattern of purifying selection after duplication occurrences, suggesting little alterations in functional divergence. The collinearity and microsynteny results revealed that the three DhPLATZ genes shared the same conserved domains as the paralogs from D. huoshanense and D. chrysotoxum. Expression profiling and quantitative analysis demonstrated that DhPLATZ genes had unique expression patterns in response to phytohormones and cold stress. Subcellular localization indicated that three DhPLATZ genes were expressed in the nucleus, suggesting their role as transcription factors. These findings enhance our understanding of PLATZ genes’ involvement in D. huoshanense species and underscore their significance as important areas for further research.